Correlations of PPARα and PPARγ expressions with 1H-MRS quantified hepatic fat content in pups of rats that experienced intrauterine growth restriction. (16th February 2021) - Wang, Tao; Chen, Pingyang; Bian, Dujun; Xiao, Enhua; Li, Dan
Abstract: Background: Proton magnetic resonance spectroscopy ( 1 H-MRS) measurement of hepatic fat content in intrauterine growth restriction rats has rarely been reported. This study was to explore the association of peroxisome proliferator-activated receptor alpha and gamma (PPARα and PPARγ) expression with 1 H-MRS quantified hepatic fat content in offspring of rats that experienced intrauterine growth restriction (IUGR). Methods and findings: IUGR was established by feeding a low-protein diet to female rats during pregnancy. Male pups of IUGR rats were weighed, liver tissues were collected at the ages of 1 day and 1, 3, 8 and 12 weeks post birth. Visceral adipose tissues (VATs) were collected at 3, 8, and 12 weeks post birth. Male pups also received conventional magnetic resonance imaging and 1 H-MRS using a 3.0 T whole-body MR scanner at 3, 8, and 12 weeks post birth. The peak area ratios in the MR spectra were calculated to determine hepatic lipid content. The expression of PPARα protein was detected by Western blot. The expression of PPARα mRNA was measured by real-time quantitative PCR. Significantly lower PPARα protein and mRNA expression were observed in liver tissues of male pups of IUGR rats at 1 day and 1, 3, 8, and 12 weeks post birth compared to male pups of control rats. In contrast, significantly higher PPARγ protein and mRNA expression were observed in VATs of male pups of IUGR rats at 3, 8, and 12 weeks post birth compared to male pups of control rats. PPARα protein and mRNA expression in the liver negatively correlated with the hepatic fat content ( r = −0.611, −0.607, respectively), whereas PPARγ protein and mRNA expression in VATs positively correlated with the hepatic fat content ( r  = 0.659, 0.668, respectively). Conclusion: 1 H-MRS allows noninvasive assessment of hepatic fat content in rats. PPARα protein and mRNA expression were significantly decreased in the livers of rats, whereas PPARγ protein and mRNA expression was significantly increased in VATs in pups of IUGR rats.